2008
DOI: 10.1021/ie8006616
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Organic Sulfur and Nitrogen Compounds in the FCC Pretreater and the FCC Unit

Abstract: The effect of hydrotreating VGO (FCC pretreatment) at different severities was examined with respect to FCC performance. Furthermore, the reaction mechanisms for conversion of the organic sulfur and nitrogen compounds found in the pretreated FCC feedstocks during FCC processing were studied. The studies were carried out under realistic conditions in a large pilot plant hydrotreating unit and in an FCC pilot plant operating with a circulating catalyst. It was found that the sulfur compounds in the FCC gasoline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 10 publications
0
28
0
Order By: Relevance
“…These steps involve treating petroleum feeds in the presence of a hydrotreatment catalyst to remove certain heteroatoms in the petroleum fractions. Of all the hetero-elements in crude oil, the sulfur has the most important effects on refiningprocesses [7][8][9][10]. Hydrotreatment catalysts are used to convert organosulfur components to hydrogen sulfide gas (H 2 S), a process known as hydrodesulfurization (HDS).…”
Section: Introductionmentioning
confidence: 99%
“…These steps involve treating petroleum feeds in the presence of a hydrotreatment catalyst to remove certain heteroatoms in the petroleum fractions. Of all the hetero-elements in crude oil, the sulfur has the most important effects on refiningprocesses [7][8][9][10]. Hydrotreatment catalysts are used to convert organosulfur components to hydrogen sulfide gas (H 2 S), a process known as hydrodesulfurization (HDS).…”
Section: Introductionmentioning
confidence: 99%
“…The sulfur chemicals used in fluid catalytic cracking (FCC) are thiols, thiophenes, sulfides, and disulfides. Therefore, dimethyl disulfide is one of the light sulfur compounds present in petroleum refinery streams. On the other hand, the insertion of high-octane oxygen-containing chemicals, known as oxygenates, into gasoline pools decreases the emissions of hydrocarbons and carbon monoxide by improving the combustion of the fuel. Thus, oxygenates have been the key organic components of reformulated gasoline, with ethanol and methyl tert -butyl ether (MTBE) being the two most widely used. , Separation process design to accomplish the removal of dimethyl disulfide needs vapor–liquid equilibrium (VLE) information on sulfur compounds in hydrocarbons and alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these efforts focused on supported CoMo sulfide catalysts, with supported NiW sulfide catalysts hardly being touched. Kordulis et al [15] reported that a NiW/c-Al 2 O 3 catalyst exhibited HDS activity comparable to that of a commercial CoMo catalyst, but higher hydrogenation and isomerization activities; more importantly, they demonstrated that the higher denitrogenation activity of the NiW-based catalysts was advantageous for the deep HDS of FCC naphtha containing nitrogen compounds that inhibit the adsorption of sulfur-containing compounds [16][17][18]. Moreover, the literature [19] shows that the promoter/M (M = W or Mo) atomic ratio can impact the HDS/HYDO selectivity.…”
Section: Introductionmentioning
confidence: 99%